PELATIHAN TEKNOLOGI ALAT MONITORING IKLIM KANDANG BAGI PETERNAK AYAM BROILER DI KEC. KAWALU, KOTA TASIKMALAYA - Edvin Priatna; Sutisna; Linda Faridah; Aripin (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2025)
The location of the Community Service Program for the Food Security Scheme is in Kec. Kawalu, Tasikmalaya City which is 8 km from Siliwangi University. One of the livelihoods of the residents of Kec. Kawalu is a broiler breeder and has five breeders. The partners of this activity are micro and small breeder companies, namly Sejahtera Mandiri and Maju Bersama and they have been operating for more than two years. The number of employees who are members of the companies of Prosperous Mandiri and Maju breeders together are 4 and 5 people, respectively. In one maintenance period, the business group raises an average of 2000 chicks per cage. The period of rearing chickens until harvest is 30-35 days. During the brooding period (the period when chicks still need brooders or need heating until they are 15 days old), the breeders provide heating facilities with wood/rice husk fuel heaters. Monitoring the cage climate such as temperature and air quality is done manually with conventional temperature and air quality measuring instruments or by observing the activity and distribution of chicks approaching/away from the heater. The problem faced by partners is that there are still many broiler breeders who do not pay attention to the condition of the chickens for monitoring temperature and air quality on a regular basis, causing a high mortality rate of broiler chickens. The purpose of this activity is to increase the knowledge, insight and skills of the broiler breeder community in the district. Kawalu in using automatic control devices and monitoring the temperature and air quality of the cage remotely. The number of participants is 5 people from members of the broiler breeder group UMK Sejahtera Mandiri and Maju together in Lewiliang Village, Kec. Kawalu, the city of Tasikmalaya. The training will be held from 29 to 30 September 2022. This activity is carried out using training, practice, and mentoring methods. The training method is to provide material on procedures for using automatic temperature monitoring control devices and ammonia gas (derived from chicken manure). The practical method is carried out by practicing automatic temperature monitoring tools and ammonia gas. The results of the training showed that the participants' interest in this activity was categorized as very good, especially for the aspect of effectiveness and practicality of broiler chicken coop climate control tools in realizing community empowerment.